Late-onset chorea after cerebral revascularization as a clinical manifestation of moyamoya disease (2021)
Moyamoya disease is a cerebral arteriopathy with an incidence of 0.086 per 100,000 inhabitants, being more common in women and Asian population. It has a broad spectrum of clinical manifestations including movement disorders, which can occur more frequently at clinical debut. The following is an unusual case of late-onset chorea after cerebral revascularization, in medical literature only 3 cases like this have been described to our knowledge. A 4-year-old girl was admitted in 2015 for focal seizures, with an unremarkable physical examination. She had no relevant data in her past pre-/perinatal history and the neurological development was normal. Brain magnetic resonance imaging (MRI) was negative to lesions. The patient was treated with carbamazepine and levetiracetam, with satisfactory seizure control. Three years later, she had acute alternating hemiparesis, and cerebral arteriography showed decreased caliber of the left middle cerebral artery and multiple small vessels of perimesencephalic and basal ganglia location. Moyamoya disease was diagnosed at that moment. Thereafter, an encephaloduroarteriosynangiosis (EDAS) was carried out obtaining a full recovery of the motor symptoms.